The properties of 70 mu m-selected high-redshift galaxies in the Extended Groth Strip - Symeonidis, M; Willner, S; Rigopoulou, D; Huang, J; Fazio, G; Jarvis, M (2008)
We examine the infrared properties of 43 high-redshift (0.1 < z < 1.2), infrared-luminous galaxies in the Extended Groth Strip (EGS), selected by a deep 70 μm survey with the Multiband Imaging Photometer on Spitzer (MIPS). In addition and with reference to starburst-type spectral energy distributions (SEDs), we derive a set of equations for estimating the total infrared luminosity (LIR) in the range 8-1000 μm using photometry from at least one MIPS band. 42 out of 43 of our sources' optical/infrared SEDs (λobserved < 160 μm) are starburst type, with only one object displaying a prominent power-law near-infrared continuum. For a quantitative analysis, models of radiation transfer in dusty media are fit on to the infrared photometry, revealing that the majority of galaxies are represented by high extinction, Av > 35, and for a large fraction (∼50 per cent) the SED turns over into the Rayleigh-Jeans regime at wavelengths longward of 90 μm. For comparison, we also fit semi-empirical templates based on local galaxy data; however, these underestimate the far-infrared SED shape by a factor of at least 2 and in extreme cases up to 10 for the majority (∼70 per cent) of the sources. Further investigation of SED characteristics reveals that the mid-infrared (70/24 μm) continuum slope is decoupled from various galaxy properties such as the total infrared luminosity and far-infrared peak, quantified by the L160/L70 ratio. In view of these results, we propose that these high-redshift galaxies have different properties to their local counterparts, in the sense that large amounts of dust cause heavy obscuration and are responsible for an additional cold emissive component, appearing as a far-infrared excess in their SEDs. © 2008 RAS.